REVISITING THE GOOGLE EFFECT: A HYBRID SYSTEMATIC REVIEW AND BIBLIOMETRIC MAPPING OF INTERNET-DRIVEN MEMORY OFFLOADING - Saefulah; Febry Marindra Cysbya Erdlanda; Lanti Mustika; Hendro Prasetyono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study undertakes a comprehensive hybrid systematic review and bibliometric analysis to examine the evolving landscape of the Google Effect, defined as the cognitive tendency to rely on digital platforms, such as search engines, as external repositories of memory. Employing rigorous PRISMA screening, the review synthesizes findings from 23 Scopus-indexed publications, mapping the conceptual progression, research trajectories, and international distribution of scholarship on this phenomenon. The bibliometric analysis reveals robust thematic linkages among cognitive offloading, memory retrieval, digital amnesia, and search behavior, underscoring the multifaceted nature of internet-driven memory practices. While foundational research predominantly characterized the Google Effect as detrimental to internal memory retention, recent studies suggest that strategic digital offloading can facilitate more efficient cognitive resource allocation, support gist memory, and enhance complex information processing. Notably, the research field remains geographically concentrated, with the majority of contributions originating from the United States and China, thus identifying a critical gap in representation from developing regions. By integrating current evidence and mapping scholarly trends, this review offers a synthesized conceptual framework that advances understanding of the Google Effect and its implications for cognitive science, digital education, and the design of technology-mediated learning environments.